Comparative aspects regarding safety and health at work in European enterprises - LEOVARIDIS, Cristina (Annals of Spiru Haret University. Economic Series, 2011)
Safety and health at work has, according to the European policies, a key role both in increasing employment, including through the prevention of premature withdrawal of employees from the labor market and in increasing competitiveness and economic performance of European enterprises. The paper makes an initial brief presentation of the main provisions of European and national policies on health and safety at work, then continues with an analysis of statistical data regarding the situation of health and safety at work for employees in EU-27. A special attention is paid to detailed analysis of recent data, from the National Institute of Statistics, on the situation concerning occupational accidents and professional diseases in our country, including factors that determine them, depending on sex, residence area, age group, economic activity, number of absence days due to health problems caused or aggravated by work.